Management of Meloidogyne hapla in Herbaceous Perennial Ornamentals by Sanitation and Resistance - Lamondia, J A (Journal of nematology, 1997)
Meloidogyne hapla can be spread in bare-root herbaceous perennial propagation material and may be difficult to control once established in new fields or in the landscape. Root pruning of bare-root plants was investigated as a means of reducing spread and establishment of M. hapla. Plants previously inoculated with 10,000 eggs/plant were root-pruned to remove either a portion or most of the fibrous root system without removing underground stems, buds, tubers, or tuberous roots. Root pruning of Aconitum, Ajuga, Anemone, Geranium, and Trollius significantly reduced or eliminated M. hapla galls and egg production in plants 1 to 4 months after propagation. Planting M. hapla-resistant plants such as Rudbeckia and Aster into pots infested with 10,000 eggs/pot eliminated M. hapla populations after 2 to 6 months of growth. Tomato plants grown after Rudbeckia and Aster were free of galls and eggs, while bioassay tomatoes grown after susceptible plants such as Coreopsis, Primula, and Lobelia were heavily galled with a large number of egg masses. These results demonstrate the potential of sanitation and resistance for management of M. hapla in perennials